Ownership Structure and Long-Run Performance of French IPO Firms - Boubaker, Sabri; Cellier, Alexis; Manita, Riadh; Toumi, Narjess (Management international / International Management / Gestiòn Internacional, 2020)
Many studies have attempted to explain the long-term underperformance phenomenon of initial public offerings (IPOs). In this paper, we use the specificities of the French market to analyze whether the control-ownership wedge explains IPO long-run performance. Moreover, we investigate whether this relationship is driven by high-tech firms. Using data from a sample of 402 French high-tech and non-high-tech IPOs that went public during 1997-2011, we find that the separation of ownership and control rights of the largest shareholder is negatively associated with long-term performance of French IPOs. This finding indicates that IPOs with disproportional ownership structure underperform other firms in the one- to five-year period following the initial offering. Such separation increases the likelihood that controlling shareholders extract private benefits of control to the detriment of minority shareholders, leading to a low long-term performance. The empirical findings also show that our conclusions are not driven by high-tech firms.